2020
DOI: 10.1002/jbmr.3952
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 Ameliorates Osteoarthritis by Activating TNFSF13B

Abstract: Epigenetic regulation is highly correlated with osteoarthritis (OA) development, whereas its role and detailed mechanisms remain elusive. In this study, we explored the expression of EZH2, an H3K27me3 transferase, in human OA cartilages and its roles in regulating OA pathogenesis. Here, we found EZH2 was highly expressed in both mice and human OA cartilage samples by using histological analysis and RNA sequencing (RNA-Seq). The medial meniscectomy (MMx) OA model results indicated the conditional knockout of Ez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…Our data now reveal that upon UTX loss, EZH2 appears to curtail chondrocytic metabolism as EZH2 RNAi-mediated suppression maintained H3K27 hypomethylated and improves ECM synthesis, whereas downregulation of EED or SUZ12 appears to stimulate matrix anabolism, as restoring EED or SUZ12 results in H3K27 hypermethylation and compromised ECM synthesis. In agreement with our data, chondrocyte-speci c EZH2 or EED knockout mice show poor cartilage development and defective bone growth 13,15 . EED thus appears functionally indispensable for trimethylation of H3K27 by EZH2 56 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data now reveal that upon UTX loss, EZH2 appears to curtail chondrocytic metabolism as EZH2 RNAi-mediated suppression maintained H3K27 hypomethylated and improves ECM synthesis, whereas downregulation of EED or SUZ12 appears to stimulate matrix anabolism, as restoring EED or SUZ12 results in H3K27 hypermethylation and compromised ECM synthesis. In agreement with our data, chondrocyte-speci c EZH2 or EED knockout mice show poor cartilage development and defective bone growth 13,15 . EED thus appears functionally indispensable for trimethylation of H3K27 by EZH2 56 .…”
Section: Discussionsupporting
confidence: 92%
“…Mice de cient in EZH1 and EZH2 in chondrocytes display poor chondrogenesis and skeletal tissue underdevelopment along with low H3K27me3 abundance 14 . Interestingly, EZH2 deletion accelerates the development of OA 15 , while chondrocyte-speci c EED knockout mice show a deformed skeleton and decreased chondrocyte survival 16 . Recently, JMJD3 is shown to regulate in vitro chondrogenic differentiation of human mesenchymal stem cells in monolayer culture 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Induction of EZH2 activates ÎČ-catenin signaling by increasing H3K27me3 on the promoter of secreted frizzledrelated protein 1 (Sfrp1) gene, a modulator of Wnt. Conditional deletion of Ezh2 in chondrocytes deteriorates OA pathological changes in the medial meniscectomy induced mouse OA model, as indicated by inhibition of chondrocyte hypertrophy through activating tumor necrosis factor ligand superfamily member 13B (TNFSF13B) (Du et al, 2020). These studies indicate that EZH2 may serve as an effective target for OA therapy.…”
Section: Histone Methyltransferases (Hmts)mentioning
confidence: 88%
“…Recently, it has been reported that Enhancer of Zest Homolog 2 (EZH2), a histone methyltransferase which adds a methyl group (-CH 3 ) on the lysine 27 of the histone 3 (H3K27), is upregulated in cartilage from OA patients, and in chondrocytes treated with IL-1ÎČ 11,12 . Furthermore, we and others have demonstrated that EZH2 inhibition reduces the methylation of H3K27 and chondrocytes hypertrophy, a process responsible for osteophytes formation 11,13,14 .…”
mentioning
confidence: 99%
“…Furthermore, we and others have demonstrated that EZH2 inhibition reduces the methylation of H3K27 and chondrocytes hypertrophy, a process responsible for osteophytes formation 11,13,14 . However, one study suggests on the contrary, that conditional knockout of EZH2 aggravates osteoarthritis development 12 .…”
mentioning
confidence: 99%